Readiness for Redress and a Sense of Self-efficacy of the Perpetrators of Violent Offences - Ewa Trojanowska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: According to the purpose of the completion of penalty it is important to foster a sense of responsibility in convicted persons. The assumption of the responsibility for the committed act is the basis for participation in mediation, one important aspect of which is redress. Therefore, it is essential to identify determinants of readiness for redress so as to be able to design social rehabilitation programmes aimed at the development of a sense of self-efficacy. One of these factors, which is subject to empirical verification, is a sense of self-efficacy. Research Aim: The aim of research consists in analysing the relationship between readiness for redress and a sense of self-efficacy of the persons who committed violent offences. Research Method: In author's own research the diagnostic survey method was used in addition to the following tools: Readiness for Restitution Scale and Generalized Self-Efficacy Scale. Results: It was found that there is a positive correlation between the readiness for undertaking corrective measures and a sense of self-efficacy of the persons serving the penalty of deprivation of liberty for the committed violent offences. A sense of self-efficacy explains variance in the readiness for redress. Nonetheless, factors other than self-efficacy make a greater contribution into explaining the variance in the dependent variable. Conclusions: The conducted research is of an exploratory nature and needs to be repeated on a larger sample of prisoners. However, the obtained results already allow to draw the conclusion that by developing one of these variables - readiness for redress or a sense of self-efficacy, the level of the other one increases at the same time. It means that these aspects can be taken into account while designing social rehabilitation programmes aimed at the social readaptation of convicts.